جدید عسکری قوت کی غرض سے سائنسی علوم کے حصول کی اسلامی اہمیت: Islamic Importance of acquiring Scientific Knowledge for the Purpose of Modern Military Power (Al-Qamar, 2022)
Allah has subjugated the universe for human beings and has attracted them to reveal the hidden secrets of the universe by using the abilities given by their Creator and Owner. In the present era, the knowledge of science and modern technology has become very important to increase the military power, and the nations that are experts in these sciences are superpowers in the world, and the nations that are behind in these sciences are weak and subdued. One of the reasons for the decline of Muslims in modern times is that they are lagging behind other nations in scientific and technological sciences, due to which they are weak compared to other nations in terms of military strength. This research paper explains the need and importance of acquiring scientific and technological knowledge to increase, strengthen and stabilize the military power among Muslims. It has been concluded from the research that acquiring knowledge of science and technology is the most important, advanced and best worship for Muslims to make the military force strong and stable for their security and to live with freedom, honor and dignity in the world. At the end of the research paper, suggestions have been made that Islam wants to see Muslims exalted in the world, so it is important for Muslims to become the cause of the exaltation of Islam by acquiring expertise in scientific and technological sciences and dominate Islam in the whole world and become exalted yourself.
Keywords: Horses; Archery; War; Technology; Skills; Training